2020
DOI: 10.1021/acs.iecr.0c03551
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Synthesis of HMF from Glucose Using the Supercritical CO2–Subcritical H2O–Isopropanol System

Abstract: 5-Hydroxymethylfurfural (HMF) is a promising building block for the production of biofuels and fine chemicals. While HMF can be derived from biomass, specifically sugars, its synthesis typically requires the use of metal-based catalysts and ionic liquids. In this study, the supercritical CO 2 −subcritical H 2 O−isopropanol system was proposed as a green reaction medium for the conversion of glucose to HMF. The response surface methodology based on the Box-Behnken design was used to investigate the effect of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…30 Protic solvents, like isopropanol and ethanol, have been successfully used both in HMF and furfural synthesis. [89][90][91][92][93] The use of a protic solvent is justified because of the beneficial suppressing effect on the formation of humic byproducts by sugar-furan condensation. [89][90][91][92][93] In fact, the in-situ formation of an alkyl-glucoside has been hypothesized to protect the sugar, suppressing parallel condensation reactions that result in the formation of humic by-products (Scheme 3).…”
Section: Protic Organic Solventsmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Protic solvents, like isopropanol and ethanol, have been successfully used both in HMF and furfural synthesis. [89][90][91][92][93] The use of a protic solvent is justified because of the beneficial suppressing effect on the formation of humic byproducts by sugar-furan condensation. [89][90][91][92][93] In fact, the in-situ formation of an alkyl-glucoside has been hypothesized to protect the sugar, suppressing parallel condensation reactions that result in the formation of humic by-products (Scheme 3).…”
Section: Protic Organic Solventsmentioning
confidence: 99%
“…[89][90][91][92][93] The use of a protic solvent is justified because of the beneficial suppressing effect on the formation of humic byproducts by sugar-furan condensation. [89][90][91][92][93] In fact, the in-situ formation of an alkyl-glucoside has been hypothesized to protect the sugar, suppressing parallel condensation reactions that result in the formation of humic by-products (Scheme 3). 89 Köchermann et al have shown that, while side reactions seem to be suppressed, the presence of ethanol below 50 vol% does not influence the rate of xylose consumption.…”
Section: Protic Organic Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Protic solvents, like isopropanol and ethanol, have been successfully used both in HMF and furfural synthesis. [64][65][66][67] The use of a protic solvent is justified because of the beneficial suppressing effect on the formation of humic byproducts by sugar-furan condensation. 64,67 In fact, the in-situ formation of an alkylglucoside has been hypothesized to protect the sugar, suppressing parallel condensation reactions that result in the formation of humic by-products (Scheme 2.3).…”
Section: Protic Organic Solventsmentioning
confidence: 99%
“…64 This approach was also successfully applied using heterogeneous and metal-free catalysis conditions, but the most promising results in terms of sugar-to-furan selectivity have been observed under homogeneous catalysis conditions. [64][65][66][67] Specifically, about 75 mol% xylose-to-furfural selectivity was obtained using a waterethanol (1:1 v-v) mixture, using H2SO4 as acid catalyst. 64 Among the alcohols, n-butanol has the specific characteristic of forming a biphasic system with water at T < 80 o C, transitioning into a monophasic system at T > 80 o C. 68 Scheme 2.3 Possible reaction pathway for the formation of the ethyl-xyloside and 2-(diethoxymethyl)-furan in a water-ethanol solvent system.…”
Section: Protic Organic Solventsmentioning
confidence: 99%